LiDARgrammetry: A New Method for Generating Synthetic Stereoscopic Products from Digital Elevation Models - Rodríguez-Cielos, Ricardo; Galán-García, José Luis; Padilla-Domínguez, Yolanda Carmen; Rodríguez-Cielos, Pedro; Bello-Patricio, Ana Belén; López-Medina, José Antonio (MDPI, 2017)
There are currently several new technologies being used to generate digital elevation models that do not use photogrammetric techniques. For example, LiDAR (Laser Imaging Detection and Ranging) and RADAR (RAdio Detection And Ranging) can generate 3D points and reflectivity information of the surface without using a photogrammetric approach. In the case of LiDAR, the intensity level indicates the amount of energy that the object reflects after a laser pulse is transmitted. This energy mainly depends on the material and the wavelength used by LiDAR. This intensity level can be used to generate a synthetic image colored by this attribute (intensity level), which can be viewed as a RGB (red, green and blue) picture. This work presents the outline of an innovative method, designed by the authors, to generate synthetic pictures from point clouds to use in classical photogrammetric software (digital restitution or stereoscopic vision). This is conducted using available additional information (for example, the intensity level of LiDAR). This allows mapping operators to view the LiDAR as if it were stereo-imagery, so they can manually digitize points, 3D lines, break lines, polygons and so on.
Keywords: Radar óptico; Fotografía panorámica; LiDARgrammetry; LiDAR; Synthetic models; Photogrammetry; Radargrammetry